The Effectiveness of A Proposed Educational Design To Develop The Systematic Thinking Skills of Students In Colleges of Education In The Subject of Curricula And Teaching Methods (Journal of the College of Basic Education, 2025)
The current research aims to investigate the effectiveness of a proposed educational design to develop the systematic thinking skills of students of colleges of education in the subject of curricula and teaching methods. The current research was limited to students of colleges of education in Iraqi universities 2024-2025. The researcher adopted an experimental design with partial control (an experimental group and a control group with a pre- and post-test). The research sample consisted of (64) male and female students from the third stage - Department of Geography. The researcher prepared a tool to measure the development of systematic thinking skills consisting of three questions, the first multiple choice, the second complete what you see fit, and the third draw diagrams that illustrate the interconnection between concepts in a systematic manner. It consisted of (60) paragraphs with the extraction of the psychometric characteristics of the test. Its validity and reliability were confirmed. To analyze the data, appropriate statistical treatments were used(spss). The results of the achievement test showed statistically significant differences in favor of the experimental group that studied using the proposed educational design. The research experiment continued for a semester. It is the first semester